(m,k)-Gur game: Exploiting message discards in order to increase the lifetime and spatial diversity in autonomic wireless sensor networks - Semprebom, T.; Zomer, G.; Milack, A.; Montez, C.; Pinto, A. R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
The main concern in Wireless Sensor Networks (WSN) algorithms and protocols are the energy consumption. Thus, the WSN lifetime is one of the most important metric used to measure the performance of the WSN approaches. Another important metric is the WSN spatial coverage, where the main goal is to obtain sensed data in a uniform way. This paper has proposed an approach called (m,k)-Gur Game that aims a trade-off between quality of service and the increasement of spatial coverage diversity. Simulation results have shown the effectiveness of this approach. © 2012 IEEE.
Keywords: Algorithms and protocols; Spatial coverage; Spatial diversity; Energy utilization; Quality of service; Systems engineering; Wireless sensor networks